Dancing off Patriarchy and Orientalism in Moroccan Pop Singer Manal's Song Niya: A Tribute to Moroccan Chikhates - Tazi, Maha (CyberOrient, 2025)
My previous work examined how pop artists in the Arab region are using self‐orientalism in their visual artworks to articulate a decolonial critique that aims to subvert the orientalist discourse through an inversion and a re‐appropriation of the colonial gaze (Tazi, forthcoming). In other words, to borrow from a famous saying by Black feminist Audre Lorde (1984), these artists are “the master's tools to dismantle the master's house.” The objective of this comment is to further expand my previous analysis on the use of self‐orientalism and neo‐orientalism in Arab pop art by looking at a different artistic genre—pop music—through the work of Moroccan pop singer Manal. I focus on both the lyrics and video clip of her song Niya (Manal l 2020 منال) which gained significant popularity and acclaim from audiences and critics alike at the time of its release in 2020 (Loubaba B 2020). I look at a selection of 15 screenshot images from the video clip where the artist uses famous Orientalist symbols such as the veil, the colonial Harem, Islamic architecture, and traditional Moroccan attire and jewelry. The analysis of the images reveals that, through a subtle contrast and a systematic interplay between lyrics and video, the artist subtly inverts and subverts both the patriarchal and Orientalist meanings behind these symbols in Niya, which translates to “naive” from Arabic, thereby articulating a decolonial feminist critique in her song.